152k views
5 votes
What is the solution of 3(4a + 2) = 2(a − 2)?

A. -1
B. -0.4
C. 0.4
D. 1

User Nav
by
5.0k points

2 Answers

7 votes

a = - 1 → A

distribute brackets on both sides of the equation

12a + 6 = 2a - 4 ( subtract 2a from both sides )

12a - 2a + 6 = - 4

10a + 6 = - 4 ( subtract 6 from both sides )

10a = - 4 - 6 = - 10 ( divide both sides by 10 )

a = - 1


User Alastair Pitts
by
6.1k points
1 vote
The answer is A and heres the work^
What is the solution of 3(4a + 2) = 2(a − 2)? A. -1 B. -0.4 C. 0.4 D. 1-example-1
User Liamness
by
5.9k points